2020
DOI: 10.24251/hicss.2020.335
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impacts of Brand Social Media Posts’ Linguistic Styles on Consumer Engagement

Abstract: Enhancing consumer engagement with brand posts on social media is challenging to digital marketers. However, it is unclear what contents work better for which brand and in what way. This paper investigates the impacts of three brand post linguistic styles (i.e., emotionality, complexity, and informality) and finds that brand posts' linguistic styles can impact consumer engagement. The findings improve our understanding of the role that language plays in brand communications on social media. Communication acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…The following graph revealed that the tweet corpus we collected contained emojis being used mostly as attitude/emotional signals (43%), followed by word substitution/repetition (37%). When we consider the emotional function of tweets (grouping the attitude and emotional signal and the attitude/emotion intensity enhancer categories), almost 60% of emojis were used to convey or reinforce emotions and/or attitudes, which may confirm previous studies such as the one conducted by McShane et al (2021), andDeng et al (2020). The former showed enhanced consumer engagement when positive emotions were conveyed by emojis.…”
Section: Página10supporting
confidence: 75%
See 3 more Smart Citations
“…The following graph revealed that the tweet corpus we collected contained emojis being used mostly as attitude/emotional signals (43%), followed by word substitution/repetition (37%). When we consider the emotional function of tweets (grouping the attitude and emotional signal and the attitude/emotion intensity enhancer categories), almost 60% of emojis were used to convey or reinforce emotions and/or attitudes, which may confirm previous studies such as the one conducted by McShane et al (2021), andDeng et al (2020). The former showed enhanced consumer engagement when positive emotions were conveyed by emojis.…”
Section: Página10supporting
confidence: 75%
“…Both Ge and Gretzel (2018) and McShane et al (2021) have shown that consumer engagement is higher when emojis are incorporated into the posts. Also, readers are more likely to 'like' posts conveying positive emotions, and thus enhance engagement through Facebook posts containing emojis, as Deng et al (2020) revealed. Such findings may account for the fact that most Brazilian brand posts in our corpus conveyed emotions and/or attitudes.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In his review, Stephen (2016) argue that linguistic style leads online consumer interaction behavior. Also, Deng et al (2020) found that brand posts' linguistic styles on social media influence consumer engagement.…”
Section: Role Of Language and Pronoun Usage In Marketing Communicationmentioning
confidence: 99%